The effect of investor sentiment on stock market liquidity under changing market conditions: evidence from South Africa - Thiasha Naidoo; Peter Moores-Pitt; Paul-Francois Muzindutsi (Cogent Economics & Finance)
The impact of investor sentiment on liquidity is profound during changing market conditions, as empirical evidence has shown that market fluctuations often trigger spikes or declines in trading volumes which have unanticipated effects on liquidity. Therefore, this study examined the time-varying effect of investor sentiment on stock market liquidity in South Africa, and employed the QARDL model to analyse monthly data and market liquidity from January 2000 to December 2023. The empirical findings indicated that investor sentiment has a short-run impact on liquidity as the market moves from bearish to bullish conditions, whilst the long-run effects are significant in a steady condition in addition to bullish and bearish market environments. The results revealed an asymmetric and quantile dependent effect of investor sentiment on stock market liquidity where investors are more pessimistic when the market is bearish, leading to decreasing liquidity. Overall, the results of this study supported the theoretical assumption that optimistic investor sentiment boosts the liquidity of the stock market whereas pessimism amongst investors decreases overall liquidity.